Pengaruh Pengungkapan Corporate Social Responsibility (CSR) terhadap Penghindaran Pajak dengan Keberadaan Direksi Wanita Sebagai Variabel Moderasi - Naufal Fachri Athalla; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to demonstrate the effect of Corporate Social Responsibility (CSR) on tax avoidance with the presence of female directors as a moderating variable. Using data from mining companies listed on the Indonesia Stock Exchange for the 2021–2023 period, this study was analyzed using moderated regression. The results show that closing CSR has an effect on tax avoidance, and the presence of female directors can strengthen this relationship in suppressing tax avoidance practices. CSR and the presence of female directors play an important role in improving corporate tax compliance. Further research is recommended to add other variables such as good corporate governance or company size, as well as expanding the sector and research period.